Apprendre à innover dans un monde incertain - Coudel, Émilie; Devautour, Hubert; Soulard, Christophe-Toussaint; Faure, Guy; Hubert, Bernard (éditions Quae, 2012)
Urged on by new expectations of society, key rural players experiment with different agricultural and food systems, showing proof of creativity and stubbornness faced with the ever-dominant mass production.But what type of sustainable development are societies seeking? How do we choose the innovations to achieve it? What role can research and public policies play to support the emergence of these innovations?